(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Nowadays there is a demand for highly qualified specialists in the field of physical education, who must not only have a high level of knowledge, but also be proficient in modern information technologies. It is absolutely clear that students of the institute of physical culture must be able to realize effectively these modern requirements within their pedagogical practice. Main issues of professional pedagogical training of specialists in the field of physical culture and sport have been investigated over the years by various authors. The aim of the investigation is to study the role of the pedagogical practice in the system of higher physical culture education. Pedagogical practice is considered an organic part of the educational process in the system of the higher physical culture education, which ensures the combination of theoretical training of future teachers with practical work, and is conducted in educational institutions. Analysis of programs of pedagogical practice allowed us to separate the following sections: organizational, cognitive, educational, methodical, tutorial, extracurricular, physical culture massive and scientific-research.